859 Improving Accuracy of Admission Notes Over A Four-Year Period Within an Orthopaedic Trauma Ward: A Four-Cycle Audit. (4th May 2021) - McCann, C; Mackenzie, S; White, T
Abstract: Background: Accurate medical notes are essential for effective patient care and safety. The Royal College of Surgeons (RCS) set forth guidelines for standards of documentation. Lack of awareness of these standards can result in inaccurate documentation, compromising patient safety. Method: Four prospective audits of admission documents for orthopaedic inpatients were completed, each 1 year apart. For each cycle, 50 admission documents were assessed to determine compliance with the RCS standards. Interventions were carried out between each audit cycle in the following order: educational posters, change from handwritten to online admission forms and optimisation of the online proforma. Results: Initially, only two criteria showed above 95% compliance. Implementing educational posters produced significant improvement in one criterion: 'note signed' (60% to 96%, p < 0.05). Moving admission documents online improved 'date stamp' (66% to 100%, P < 0.05) and 'contact number' (0% to 34%, p < 0.05), but decreased documentation of 'time recorded' (18% to 0%, p < 0.05) and 'name and grade' (74% to 26%, p < 0.05). Further education and modification to the admissions proforma improved documentation of all criteria to over 95%. Conclusions: Early cycles of this audit highlighted poor standards of documentation in admission records. Changing to online patient records significantly changed documentation standards. These were further improved with educational measures.